Blindness and children : an individual differences approach - Warren, David H. (Cambridge University Press, 1994)
"A summary and interpretation of the research literature on infants and children with visual impairments. It concludes that many aspects of delayed development are the result not of visual impairment itself, but of an environmental variables that tend to accompany visual impairment."
Keywords: Blind children.; Children with disabilities -- Development.; Blindness.; Child development.; Infants.; Children.; Blindness; Child Development; Infant; Child; Enfants aveugles.; Enfants handicapés -- Développement.; Cécité.; Enfants -- Développement.; Nourrissons.; Enfants.; Enfance.; blindness.; infants.; children (people by age group); childhood.; FAMILY & RELATIONSHIPS -- Children with Special Needs.; Infants; Children; Child development; Blind children; Children with disabilities -- Development; Kind; Entwicklung; Blindheit; Blindheid.; Kinderen.; Individuele verschillen.; Deficientes fisicos.